Racial/Ethnic Inequalities in the Distribution of Income in Colombia: Analysis by Quantile Regression - Correa Fonnegra, Juan Byron; Viáfara López, Carlos Augusto; Zuluaga González, Víctor Hugo (Sociedad y Economía, 2010)
This work analyzes the wage gap at different points in the conditional distribution of income according to ethnic or racial status using data from the National Household Survey of December 2000. The methodology involves the estimation of Mincer-type equations, including correction of the endogeneity bias present in these equations and uses the methodology of disaggregation according to Melly (2005). The findings show a predominant effect of the “unexplained” proportion of the wage gap between Colombians of African descent and the rest of the population which could be the result of racial discrimination.